A data-driven reconstruction of Horndeski gravity via the Gaussian processes. Issue 9 (14th September 2021) - Bernardo, Reginald Christian; Levi Said, Jackson
Abstract: We reconstruct the Hubble function from cosmic chronometers, supernovae, and baryon acoustic oscillations compiled data sets via the Gaussian process (GP) method and use it to draw out Horndeski theories that are fully anchored on expansion history data. In particular, we consider three well-established formalisms of Horndeski gravity which single out a potential through the expansion data, namely: quintessence potential, designer Horndeski, and tailoring Horndeski. We discuss each method in detail and complement it with the GP reconstructed Hubble function to obtain predictive constraints on the potentials and the dark energy equation of state.